Major Depression Duration Reduces Appetitive Word Use: An Elaborated Verbal Recall of Emotional Photographs - Capecelatro, Maria R. (2013)
INTRODUCTION: Major depressive disorder (MDD) is characterized by cognitive biases in attention, memory and language use. Language use biases often parallel depression symptoms, and contain over-representations of both negative emotive and death words as well as low levels of positive emotive words. This study further explores cognitive biases in depression by comparing the effect of current depression status to cumulative depression history on an elaborated verbal recall of emotional photographs. METHODS: Following a negative mood induction, fifty-two individuals (42 women) with partially-remitted depression viewed – then recalled and verbally described – slides from the International Affective Picture System (IAPS). Descriptions were transcribed and frequency of depression-related word use (positive emotion, negative emotion, sex, ingestion and death) was analyzed using the Linguistic Inquiry and Word Count program (LIWC). RESULTS: Contrary to expectations and previous findings, current depression status did not affect word use in any categories of interest. However, individuals with more than 5 years of previous depression used fewer words related to positive emotion (t(50) = 2.10, p = .04, (d = .57)), and sex (t(48) = 2.50, p = .013 (d = .81)), and there was also a trend for these individuals to use fewer ingestion words (t(50) = 1.95, p = .057 (d = .58)), suggesting a deficit in appetitive processing. CONCLUSIONS: Our findings suggest that depression duration affects appetitive information processing and that appetitive word use may be a behavioral marker for duration related brain changes which may be used to inform treatment.